Smad2/4 Signaling Pathway Is Critical for Epidermal Langerhans Cell Repopulation Under Inflammatory Condition but Not Required for Their Homeostasis at Steady State - Huang, Linting; Li, Gui-Hua; Yu, Qian; Xu, Yingping; Cvetkovski, Steven; Wang, Xuan; Parajuli, Nirmal; Udo-Inyang, Imo; Kaplan, Daniel; Zhou, Li; Yao, Zhirong; Mi, Qing-Sheng (Frontiers in Immunology, 2020)
Epidermal Langerhans cells (LCs) are skin-resident dendritic cells that are essential for the induction of skin immunity and tolerance. Transforming growth factor-β 1 (TGFβ1) is a crucial factor for LC maintenance and function. However, the underlying TGFβ1 signaling pathways remain unclear. Our previous research has shown that the TGFβ1/Smad3 signaling pathway does not impact LC homeostasis and maturation. In this study, we generated mice with conditional deletions of either individual Smad2, Smad4, or both Smad2 and Smad4 in the LC lineage or myeloid lineage, to further explore the impact of TGFβ1/Smad signaling pathways on LCs. We found that interruption of Smad2 or Smad4 individually or simultaneously in the LC lineage did not significantly impact the maintenance, maturation, antigen uptake, and migration of LCs in vivo or in vitro during steady state. However, the interruption of both Smad2 and Smad4 pathways in the myeloid lineage led to a dramatic inhibition of bone marrow-derived LCs in the inflammatory state. Overall, our data suggest that canonical TGFβ1/Smad2/4 signaling pathways are dispensable for epidermal LC homeostasis and maturation at steady state, but are critical for the long-term LC repopulation directly originating from the bone marrow in the inflammatory state.